Desindactilización del 4° y 5° dedo con injerto antólogo de piel del tobillo - Pérez del Pozo, María Del Carmen; Villa Fuertes, Alejandro; Soriano Medrano, Alfredo; Martínez Boix, Cristina; Trepal, Michael J. (Revista Internacional de Ciencias Podológicas, 2007)
For a good surgical treatment of desyndactyly a good presurgical planning must be made to decrease the complications intra and post surgical. It is important to inform to the patient the surgical treatment purpouse and to leave in a background the aesthetic result due to the patient can feel fear and unconformed with the scars.